Nakazy i zakazy rodzicielskie a kreatywność jednostki. Źródła inhibitorów twórczości w perspektywie analizy transakcyjnej - Dorota Gębuś (Edukacyjna Analiza Transakcyjna, 2016)
Striving for self-realization is a natural human need that appears in the course of their develop- ment. It becomes visible while an individual is engaged in creative activities whose aim is to change and improve oneself and one's environment. This natural tendency is usually hindered be- cause of various barriers. This article is an attempt to describe how these barriers come into beingwith particular emphasis on parents’ drivers and injunctions, which are analysed from the perspec- tive of transactional analysis.